Estrés aculturativo y desesperanza en migrantes venezolanos de las ciudades de Arequipa y Tacna - Romero Huaraca, Pierina del Rosario (2024)
In an increasingly interconnected world, studying the phenomenon of migration becomes particularly relevant due to its complex associations with psychosocial factors. The present study, aimed to identify the relationship between acculturative stress and hopelessness in a sample of Venezuelan migrants to Peru. An empirical investigation with an associative strategy and simple correlation design was carried out (Ato et al., 2013), the sample was made up of 266 Venezuelan migrants aged 18 to 75 years from the cities of Arequipa and Tacna that make up part of Southern Peru. The instruments used were the Barcelona Immigrant Stress Scale (BISS) and the Beck Hopelessness Scale (BHS). The results have determined that there is a very significant and direct correlation between acculturative stress and hopelessness (r=.16; p<.01), with a small effect size (r2 =.03). On the other hand, it is verified that the greater the culture shock, the greater the feeling about the future (r=.19; p<.01; r2 =.03), the greater the loss of motivation (r=.25; p< .001; r2 =.06;) and expectation about the future (r=.26; p<.001; r2 =.06), all with a small effect size. It is recommended that actions be taken to promote the development of intrinsic protective factors that allow better adaptability to the diversity of the migrant population.